Efectividad de la terapia cognitiva basada en el mindfulness (MBCT) en el tratamiento de la depresión en adultos: revisión aplicada - Blair Sarmiento, Ana Maria (2023)
Depression is one of the most common mental disorders affecting 5% of the adult population in the world. On the other hand, mindfulness-based cognitive therapy (MBCT) is shown to be an effective tool in increasing cognitive flexibility, improving cognitive deficits, in the prevention of relapse and reduction of depressive symptoms, in people with chronic, recurrent depression or with resistance to treatment. For this reason, the main objective of this report is to investigate the effectiveness of MBCT in reducing depressive symptoms. A search was carried out in the Web of Science, EBSCOhost, SCOPUS and ProQuest databases, following the PRISMA criteria, where 10 articles that investigated the effectiveness of MBCT on depression were selected; either as exclusive therapy or complementary to other treatments. In the results, it was found that MBCT is effective in reducing depressive symptoms, both major and recurrent depression, in people with chronic, recurrent depression or with resistance to treatment. As secondary results, MBCT contributes to better levels of protective factors such as self-compassion and mindfulness skills.